Pengembangan Media Pembelajaran Booklet Pada Materi Menulis Surat Pribadi Berbasi Direct Instruction di SMP Negeri 2 Gunungsitoli - Hasrat Kristiawan Telaumbanua; Lestari Waruwu; Mastawati Ndruru (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this research is to develop a decent, practical, and effective Direct Instruction-based booklet learning media. This research is development research using the ADDIE model which consists of Analysis, Design, Development, Implementation, Evaluation. Booklet development research was carried out at SMP Negeri 2 Gunungsitoli. The results of the research are in the form of Direct Instruction-based booklet products on personal letter writing material. The results of the questionnaire assessment of individual trial student responses obtained a score of 97.7% in the very practical category. In the small group trial, a score of 98.5% was obtained in the very practical category. In the field trial, a score of 90.1% was obtained in the very practical category. Assessment of student learning outcomes tests obtained a percentage of classical completeness in individual trials of 95.0% very effective category. In the small group trial 95.05 the category was very effective. In field trials 94.1% category is very effective. So, the research above, it was concluded that the Direct Instruction-based booklet learning media is feasible, practical, and effective to use so that it fulfills the research objectives.